An analysis of the quality of investigative interviews with children in France: age of the witness does matter. (25th January 2021) - Verkampt, Fanny; Dodier, Olivier; Milne, Rebecca; Ginet, Magali
ABSTRACT: A context-driven analysis was performed to assess the quality of French investigative interviews with three age groups of child witnesses (under 7 years old, 7–10 years old, and 11–17 years old). We measured how age was related to the quality of 24 real-life interviews by evaluating how child-centered the interview was: (i) did it follow recommendations for each phase of the interview and, (ii) was the questioning style appropriately adapted to the child's previous answer. Results showed that the older children gave more detailed responses to open questions. However, investigators did not encourage their recall through the use of appropriate questions, but instead asking closed and leading questions. With the younger children, interviewers also asked predominantly closed and leading questions but after evasive answers. Our findings suggest different strategies underpin the use of inappropriate questions with respect to the age of the witnesses. Implications for training are discussed.